Outcomes of Micropulse Transscleral Cyclophotocoagulation in Uncontrolled Glaucoma Patients. Issue 3 (March 2019) - Zaarour, Karen; Abdelmassih, Youssef; Arej, Nicolas; Cherfan, Georges; Tomey, Karim F.; Khoueir, Ziad
Abstract : Purpose: This study aimed at evaluating the intermediate-term efficacy and safety of micropulse transscleral cyclophotocoagulation (MP-TSCPC) in cases of uncontrolled glaucoma. Methods: Patients with moderate to advanced glaucoma and uncontrolled intraocular pressure (IOP) despite maximally tolerable antiglaucoma medications were selected to undergo MP-TSCPC using the MP3 handpiece with the Iridex Cyclo G6 (IRIDEX Laser Systems). Follow-up examinations took place on a regular basis until 15 months postoperatively. Results: Seventy-five eyes of 69 patients (53.6% male patients) were included. Mean age was 55.5±22.9 years. Primary open-angle glaucoma was the most common diagnosis. Corrected distance visual acuity at baseline ranged between 0 and 2.1 logMAR. Mean prelaser IOP was 26.0±7.91 mm Hg. This was reduced significantly to 13.8±5.6 mm Hg (44.0% reduction, P <0.001) at week 1, and to 18.0±7.7, 18.4±7.1, 16.7±6.2, 15.1±4.1, 15.7±5.32, and 14.8±5.50 mm Hg at months 1, 3, 6, 9, 12, and 15, respectively. The mean number of antiglaucoma drops decreased significantly up to 12 months of follow-up ( P =0.008) and that of oral acetazolamide tablets decreased significantly up to 15 months ( P <0.001). The success rate decreased progressively with time, reaching 81.4% at 6 months and 73.3% at 1 year. No major postoperative complications were encountered, and no eye lost vision completely. Conclusions: MP-TSCPC is an efficient noninvasive glaucoma treatment that achieves sustained IOP reduction and reduced need for ocular antihypertensive medications for up to 15 months. The optimal laser parameters to achieve the best success rate with the least side effects still need to be determined.